FROM IDEALS TO EVERYDAY PRACTICE: INTERNALIZING PANCASILA VALUES IN STUDENTS’ SOCIAL BEHAVIOR - Bambang Yuniarto (International Journal of Teaching and Learning, 2026)
This study investigates the relationship between the internalization of Pancasila values and the social behavior of senior high school students in Cirebon City, Indonesia. Despite Pancasila's constitutional centrality as the philosophical and moral foundation of Indonesian national life, empirical evidence linking ideological value internalization to observable behavioral outcomes among students remains limited. Employing a quantitative cross-sectional survey design with an explanatory approach, the study recruited 412 students from six senior high schools through stratified cluster random sampling. Data were collected using a validated structured questionnaire measuring two primary constructs: internalization of Pancasila values, operationalized as a second-order reflective–formative construct comprising three lower-order dimensions (belief, attitude, and practice), and students' social behavior, encompassing cooperation, tolerance, respect, and responsibility. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Measurement model evaluation confirmed satisfactory convergent validity, discriminant validity, and composite reliability across all constructs. Structural model results revealed that the internalization of Pancasila values exerts a significant and positive influence on students' social behavior, explaining approximately 37.7% of its variance, with a large effect size. Second-order construct analysis demonstrated that belief constitutes the strongest formative dimension of value internalization, followed by attitude and practice a hierarchy that exposes a critical internalization gap in which cognitive endorsement of national values consistently outpaces their behavioral enactment. The findings underscore the inadequacy of knowledge-transmission approaches to character education and highlight the urgent need for pedagogical strategies that actively bridge ideological conviction and observable social conduct. This study contributes an empirically validated measurement model of Pancasila value internalization and advances the application of hierarchical SEM approaches in civic and values education research, with implications extending to broader international discourse on global citizenship and character education.